Knowledge, utilisation and perception regarding Ayushman Bharat Pradhan Mantri Jan Arogya Yojana among Mysuru residents: insights from a cross-sectional analysis - K., Shruddha; R., Deepshika; M., Rakesh; M., Shwethashree (International Journal Of Community Medicine And Public Health, 2025)
Background: Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) is among the largest government-funded health insurance schemes globally, aimed at providing financial protection for secondary and tertiary healthcare to economically vulnerable populations. Awareness and understanding are crucial for the scheme’s successful implementation and optimal utilization. Objectives were to assess the knowledge, utilization, and perception regarding AB-PMJAY among Mysuru residents and examine associated sociodemographic factors. Methods: A community-based cross-sectional study was conducted in Mysuru over a period of two months, from December 2024 to February 2025. A total of 350 participants were selected through simple random sampling. A semi-structured questionnaire was used to collect information on socio-demographic data, awareness, and utilization of AB-PMJAY. Data were analysed using SPSS version 30. Descriptive and inferential statistics were applied, and p<0.05 was taken as statistically significant. Results: Among the participants, 55.7% had poor awareness, 30.9% had average awareness, and only 13.4% had good awareness of AB-PMJAY. Utilization of scheme benefits was reported by 33.7% of respondents, while 66.3% had not availed any services. Regarding perceptions, 38.0% felt the scheme had improved healthcare access, 6.6% disagreed, and 55.4% were uncertain. A statistically significant association (p=0.011) was observed between awareness and monthly household income, with higher awareness among those earning less than ₹5000. Conclusions: The study highlights suboptimal awareness and utilization of AB-PMJAY among Mysuru residents. Targeted awareness campaigns and community engagement strategies are essential to enhance public understanding and uptake of the scheme.